Концептуальная модель регламентной поддержки развития интеллектуального потенциала персонала предприятия - Шаталова, Т.С. (Економіка промисловості, 2012)
Розглянуто проблему моделювання регламентної підтримки розвитку інтелектуального потенціалу персоналу підприємства. Встановлено основні передумови регламентації системи управління персоналом. Наведено концептуальну модель регламентної підтримки розвитку інтелектуального потенціалу персоналу підприємства.
Ключові слова: підприємство, персонал, інтелектуальний потенціал, регламентна підтримка. Рассмотрена проблема моделирования регламентной поддержки развития интеллектуального потенциала персонала предприятия. Определены основные предпосылки регламентации системы управления персоналом. Представлена концептуальная модель регламентной поддержки развития интеллектуального потенциала персонала предприятия.
Ключевые слова: предприятие, персонал, интеллектуальный потенциал, регламентная поддержка. The absence of regular management in the control and development of staff causes significant losses of time and material resources in this sphere, underestimation of importance of leadership development functions of staff and its intellectual potential, poor quality of legal, information, training and methodological support of staff training processes that doesn’t allow systematic learningwith planned character, demonstrating the need to create and introduce new effective and reliable approaches and management practices in staff management and development sphere. Therefore, the development of regulatory support for managing staff and its intellectual potential for effective formation, development and training the enterprise staff on the basis of a set of related regulations is a major challenge for local enterprises.
The purpose of this study is to develop a conceptual model of regulatory support for staff intellectual potential development at an enterprise that will provide an integrated system and infrastructure for training and development, and will reduce the cost of their operation. The object of study is the processes of staff intellectual potential development at an enterprise. The subject of the study is theoretical and methodological framework, mechanisms and methods of improving regulatory support for staff intellectual potential development at an enterprise. The methodological basis of the study is the works of local and foreign scientists in the field of system approach, general systems theory and the theory of adaptive management, as well as theory and practice of human resource management, its development and training, economic and mathematical modeling, tools and information technologies in managerial decisions.
The principal possibility of shifting regulatory support and development for staff intellectual potential development at an enterprise into various states by selecting the appropriate managerial actions and bringing it to the practical implementation allows considering the system of regulatory support as the control object that requires solving a number of theoretical problems.
The first task is to assess the current state of the system, the second is related to the defining the control objectives for the system of regulatory support for staff intellectual potential development at an enterprise, defining the final state of the system, the third one is to identify achievable goals and form the set of feasible states. Basing on the set provisions, the process on modelling the regulatory support for staff intellectual potential development at an enterprise may be represented in the form of two loops – the description of staff management system, due to the need to analyze the current state of support system of staff intellectual potential development, as well as comprehensive analysis of the staff management system. As a part of the control loop of regulatory support system for staff intellectual potential development at an enterprise, basing on the incoming information, and given the current limitations on available resources, the set of feasible states is formed.
The proposed conceptual model of regulatory support for staff intellectual potential development at an enterprise will provide the fundamental possibility forthe comprehensive examination and improvement of regulatory support using formal methods, procedures and criteria, and will also identify the structure and the main interconnections of the system.
Keywords: enterprise, staff, intellectual potential, regulations.